The DNA restart : unlock your personal genetic code to eat for your genes, lose weight, and reverse aging - Moalem, Sharon (Rodale Books, 2016)
"The DNA Restart turns traditional dietary advice on its head with groundbreaking research that demonstrates that we all require different diets based on our genes. In The DNA Restart, Sharon Moalem, MD, PhD, provides a revolutionary step-by-step guide to the diet and lifestyle perfect for your individual genetic makeup. A physician, scientist, neurogeneticist, and New York Times bestselling author, Dr. Moalem has spent the last two decades researching and formulating how to reset your own genetic code using five essential pillars: eat for your genes; reverse aging; eat umami; drink oolong tea; and slow living. The DNA Restart plan utilizes decades of in-depth scientific research into genetics, epigenetics, nutrition, and longevity to explain the pivotal role genes play in the journey to ideal weight and health status. Dr. Moalem's unique 28-day plan shows how to upgrade sleep, harness sensory awareness, and use exercise to reset your DNA; how to determine the right amounts of protein, carbs, and fats you need for your individual genetic make-up; and how to incorporate umami-rich recipes and oolong tea into your diet to genetically thrive. Delicious recipes with mix-and-match meal plans, inspiring testimonials, and genetic self-tests round out this paradigm shifting diet book"--